APPLYING GUESSING GAME FOR TEACHING VOCABULARY AT CLASS VII OF SMPN 1 BELIMBING - Gregorius Olla; Thomas Joni Verawanto Aristo (STKIP Persada Khatulistiwa Sintang, 2026)
This research aims to improve students' learning abilities in learning vocabulary at SMPN 1 Belimbing, especially in class VII by used guessing game techniques. The researcher used this technique because based on initial observations there were several problems faced by students such as lack of motivation and lack of vocabulary so that they were not interested in learning English. Therefore, the researcher used a guessing game technique so that students were interested in participating in the learning process. In this research, the researcher used the classroom action research method. Furthermore, for data collection, the research techniques used were observation, interviews and documents. Furthermore, in the research instrument, the researcher used tools in the form of observation sheets, field notes, interview guidelines, tests and cameras. The last is data analysis techniques in the form of data collection, data coding, and comparing data, constructing meaning and interpretation and responding to results. The results obtained by researcher from two cycles carried out are in cycle 1 with a total percentage of 85.15% and cycle 2 with a total percentage of 88.65%. Based on the results in both cycles, it can be seen that students are very interested and motivated to participate in the learning process. From the results obtained in this research, it can be said that this research has been successfully carried out. So it can be said that the guessing game technique can have a very good impact in providing learning material, especially vocabulary. Keywords: Games, Guessing Game, Teaching and Vocabulary